Long-run consequences of natural disasters: Evidence from Tangshan - Guo Xu (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Exploiting Tangshan 1976 - the deadliest earthquake in the 20th century - as a source of exogenous variation, we estimate the long-run effect of a historical shock on contemporary socio-economic outcomes. Cohorts born after the earthquake were not only larger, but exhibit lower school completion rates, particularly among the female today. Despite lower schooling levels, there is no evidence for adverse labour market outcomes. We conduct robustness checks and argue that the effect is causal.
Keywords: I20; J00; O18; 330; environmental shock; earthquake; natural disaster; education; fertility; Erdbeben; Bildungsverhalten; Fruchtbarkeit; China